Efficiency of Selected Sudanese Sheep Markets: A Bivariate Approach (1995-2011) - A., Mohammed O.; A, Murtada Kh. (Gezira Journal of Economic and Social Sciences, 2016)
o achieve the objectives of this paper, the following questions were attempted to be answered: 1- Were the sheep prices data in the Sudan had stationarity properties over time? 2- Was there any co integration between these markets in the short and long run?       The data used for this paper covered selected Sudanese Sheep Markets, for the period (1995-2011 ).     The results reveal that the market of sheep affected each other except the sheep prices of Nyala market which separated of other markets excluding Medani. This result seems to be reasonable, because of the recent paved roads that linked between all these markets which accelerated and facilitated the movement between these markets, in addition to a huge capital that specified toward livestock business recently.